The overview of an overview of NiCo/SiO2 for CO2 methanation: effect of calcination temperature / Nur Khalilah Mohd Taib @ Hashim and Siti Aminah Md Ali - Mohd Taib @ Hashim, Nur Khalilah; Md Ali, Siti Aminah (2020)
The studies is made to review and identify the previous researches on NiCo/SiO2 catalyst for CO2 methanation with the effect of calcination temperature. CO2 methanation is the process to reduce the emission of anthropogenic gas which is carbon dioxide by the combination with hydrogen to produce methane gas. The review had been made based on the previous research on nickel-based catalyst, nickel-cobalt catalyst and the effect of calcination temperature on the catalyst. Most of the research stated that the catalyst was prepared by impregnation. After the preparation of catalyst, some of researches tested the catalyst first. The characterization of the catalyst had been made N2 adsorption – desorption isotherms using BET, X-ray powder diffraction (XRD), temperature programmed reduction (TPR), temperature programmed desorption of H2 (H2-TPD), and CO2 (CO2-TPD). For nickel-based catalyst, the result obtained from the researches involve the nickel content in the catalyst. The amount of nickel content can affect the specific surface area, crystalline size, pore size distributions and CH4 selectivity. The performance of the particle also increased. The better selection of the catalyst is the catalyst must have a good reducibility of catalyst, large specific surface area and high CO2 conversion and CH4 selectivity. The bigger pores can allow the easier diffusion of water and air molecules. The research will undergo the process at the different reaction temperature in order to study the effect of calcination temperature. The most common calcination temperature that used in the research is between 250℃ to 900℃. The catalyst at different calcination temperature resulting in different characteristics and performance of the catalyst. The different calcination temperature used gave the different characteristics of the catalyst. Some researchers found that the optimum calcination temperature is above 500 ℃. The optimum calcination temperature will give the better catalytic performance of the catalyst. Nickel based catalyst is the commonly used catalyst due to its performance and low cost. The metal loading in catalyst can affect the catalytic performance. The catalyst activity and characteristics also can be affected by reaction temperature and composition. The propose to increase the stability of the catalyst is by adding some catalyst addictive. The catalyst addictive also can be added to increase the stability of the catalyst. From the review, the conclusion can be made by observing the result obtained from the characterization. The proper selection of support catalyst also can affect the characterization of the catalyst.